ALLOPHONIC SPLITS IN L2 PHONOLOGY: THE QUESTION OF LEARNABILITY - Eckman, Fred R.; Elreye, Abdullah; Iverson, Gregory K . (International Journal of English Studies, 2001)
The research reported in this paper is intended as a contribution to the understanding of several wellknown problems relating to the leaming of phonemic contrasts in second language (L2) phonology. The paper describes a series of ongoing studies examining what Lado (1957) hypothesized to represent maximum diffículty in second language pronunciation, narnely, a phonemic split. This is the process involved when an L2 learner must split native language (NL) allophones into separate target language (TL) phonemes. Two core principles of phonological theory are described and evaluated for their relevante in explaining the series of well-defined, implicationally-related stages involved in a phonemic split. Finally, the paper reports the results of an empirical study designed to test the explanatory adequacy of these principles, and concludes with a discussion of the implications of these studies for second language phonology in general.